KEPUASAN BELAJAR PEMBELAJARAN DARING PADA MAHASISWA PRODI S1 KEPERAWATAN STIKES HORIZON KARAWANG - Lilis Suryani (ITB AAS INDONESIA Surakarta, 2022)
In the midst of the COVID-19 pandemic, one of the steps of utilizing network technology and information technology in universities is by online learning. Online learning is the best solution for teaching and learning activities. with online learning, it will provide students with the opportunity to be able to take a lesson or course, although with online learning can still provide quality learning services for students. With online learning, it is hoped that it can provide satisfaction to students will carry out the learning process. The purpose of this research is to find out the influence of online learning on the learning satisfaction of undergraduate students of Nursing Stikes Kharisma Karawang. The type of research to be used is quantitative research. Descriptive analysis research design with cross sectional approach with respondents of all students of S1 Nursing Stikes Kharisma Karawang study program which amounted to 527 students. The results showed that as a large number of respondents stated that the learning process is quite good, as a large number of respondents feel quite satisfied with the online learning conducted during the covid-19 pandemic, and there is an influence of the learning process on the satisfaction of undergraduate nursing students reviewed from the dimension of satisfaction at STIKES Karisma Kawawang. Keywords : online learning, student satisfaction